Two-years Biannual Evaluation of Drug-resistant Tuberculosis Patients Completing Their Treatment at Persahabatan General Hospital Jakarta - Murniati Murniati; Diah Handayani; Fathiyah Isbaniah (Indonesian Society of Respirology (ISR), 2020)
Background: Drug-resistant tuberculosis (DR-TB) is a worldwide threat, including in Indonesia, which course of treatments are time consuming and are expensive. Recent findings suggest trends in recurrence of DR-TB, while no data is available to summarize the recurrence of DR-TB in Indonesia. Objective: This study aimed to evaluate DR-TB patients which was biannually performed for two-years (e.g. at the 6th, 12th, 18th, and 24th mos) after treatment completion. Methods: This cross-sectional study involved DR-TB patients completing their treatment at Persahabatan General Hospital Jakarta, Indonesia, between April and December 2017. The post-treatment evaluation during the 6th, 12th, 18th, and 24th mos included clinical, chest x-ray (CXR) and sputum culture examination. Results: Sixty patients were observed in this study, 31 (51.7%) were males and 29 (48.3%) were females. The mean age was 42.3+12.5 yo and the mean body mass index was 21.75+4.34. Fourty nine (81.7%) patients showed extensive lesions per CXR and none of the patient showed Mycobacterium tuberculosis growth per sputum culture. Conclusion: There was no recurrence of DR-TB from patients completing their treatment at Persahabatan General Hospital Jakarta, Indonesia during two-years post-treatment evaluation.